Measurement of large angle Rayleigh scattering cross sections for 39.5, 40.1 and 45.4 keV photons in elements with 26 ≤ Z ≤ 83. (October 2017) - Upmanyu, Arun; Singh, Gurjot; Duggal, Heena; Kainth, H.S.; Bhalla, Atul; Kumar, Sanjeev
Abstract: The present work reports Rayleigh scattering cross section measurements for the 39.5 keV (Sm- Kα 2 ), 40.1 keV (Sm- Kα 1 ) and 45.4 keV (Sm- Kβ 1, 3 ) X-ray photons in 35 elements with 26 ≤ Z ≤ 83 at backward angle of 139°. The scattering measurements were performed in reflection mode geometrical set up involving a secondary photon source consisting of Samarium (62 Sm) target excited by the 59.54 keV γ-rays from the 241 Am radioactive source. The scattered photons were detected using a low energy germanium (LEGe) detector. The product of detector efficiency, intensity of incident photons and other geometrical factors were determined by measuring the K X-ray yields from targets with 47 ≤ Z ≤ 59 and knowledge of the respective K X-ray fluorescence cross sections. The measured cross sections are compared with the theoretical cross sections based on the modified form factor (MF) formalisms and the second-order S-matrix approach. The experimental results demonstrate large deviations from the MF values for the elements with K shell binding energy (B K ) in vicinity of the incident photon energy (E in ), which smooth out with inclusion of the anomalous scattering factors (ASFs). The S-matrix values, in general, agree with the measured cross sections for all the elements under investigation. Highlights: Rayleigh scattering cross sections for the62 Sm (Kα2, Kα 1 & Kβ 1, 3 ) X-rays at 139° with 26 ≤ Z ≤ 83 are measured. The scattering cross sections based on the MFASF are in general higher for up to 7% for the medium- and high-Z elements. The S-matrix values exhibit in general good agreement with the measured cross sections.